High-Capacity and Long-Lifespan Aqueous LiV3O8/Zn Battery Using Zn/Li Hybrid Electrolyte - Qiang Pang; Xiangyu Yu; Shijing Zhang; Wei He; Siyu Yang; Yao Fu; Ying Tian; Mingming Xing; Xixian Luo (Nanomaterials, 2021)
Aqueous zinc-ion batteries (AZIBs) are promising candidates for large-scale energy storage because of their low cost and high safety. However, their practical applications are impeded by low energy density and short service life. Here, an aqueous Zn2+/Li+ hybrid-ion battery is fabricated using the LiV3O8 nanorods as the cathode, metallic Zn as the anode, and 3 M Zn(OTf)2 + 0.5 M LiOTf aqueous solution as the electrolyte. Compared with the batteries using pure 3 M Zn(OTf)2 electrolyte, the cycle performance of the hybrid-ion battery is significantly improved. After 4000 cycles at 5 A g1, the remaining capacity is 163.9 mA h g−1 with impressive capacity retention of 87.0%. Ex-situ XRD, ex-situ XPS, and SEM tests demonstrate that the hybrid electrolyte can inhibit the formation of the irreversible Zn3(OH)2V2O7·2H2O by-product and restrict Zn dendrite growth during cycling, thereby improving the cycle performance of the batteries.